The effect of short fiber composite base on microleakage and load-bearing capacity of posterior restorations - Sufyan K. Garoushi; Marwa Hatem; Lippo V. J. Lassila; Pekka K. Vallittu (Taylor & Francis Group, 2015)
Objectives: To determine the marginal microleakage of Class II restorations made with different composite base materials and the static load-bearing capacity of direct composite onlay restorations. Methods: Class II cavities were prepared in 40 extracted molars. They were divided into five groups (n = 8/group) depending on composite base material used (everX Posterior, SDR, Tetric EvoFlow). After Class II restorations were completed, specimens were sectioned mid-sagitally. For each group, sectioned restorations were immersed in dye. Specimens were viewed under a stereo-microscope and the percentage of cavity leakage was calculated. Ten groups of onlay restorations were fabricated (n = 8/group); groups were made with composite base materials (everX Posterior, SDR, Tetric EvoFlow, Gradia Direct LoFlo) and covered by 1 mm layer of conventional (Tetric N-Ceram) or bulk fill (Tetric EvoCeram Bulk Fill) composites. Groups made only from conventional, bulk fill and short fiber composites were used as control. Specimens were statically loaded until fracture. Data were analyzed using ANOVA (p = 0.05). Results: Microleakage of restorations made of plain conventional composite or short fiber composite base material showed statistically (p < 0.05) lower values compared to other groups. ANOVA revealed that onlay restorations made from short fiber-reinforced composite (FRC) as base or plain restoration had statistically significant higher load-bearing capacity (1593 N) (p < 0.05) than other restorations. Conclusion: Restorations combining base of short FRC and surface layer of conventional composite displayed promising performance related to microleakage and load-bearing capacity.